ANTIMICROBIAL RESISTANCE OF Enterococcus spp. ISOLATED FROM ANIMAL-DERIVED FOOD - Milanov, Dubravka; Vidaković Knežević, Suzana; Vranešević, Jelena; Dončić, Stefan; Knežević, Slobodan; Aleksić, Nevenka (Food and Feed Research, 2025)
The current work aims to test the antimicrobial resistance of 92 Enterococcus spp. isolates from dairy products, eggs and meat in the Autonomous Province of Vojvodina, Serbia. As confirmed by PCR or MALDI TOF, E. faecalis was the most frequently encountered species (51.08%), followed by E. faecium (39.13%), E. hirae (6.52%), E. thailandicus (2.17%) and E. durans (1.08%). Generally, the most frequent resistance phenotype in all isolates was to tetracycline (34.78%), erythromycin (27.17%), doxycycline (21.73%) and streptomycin (13.04%). The phenotypic resistance to antimicrobials was less prevalent in enterococci isolates from dairy products than in meat isolates. Out of the 92 enterococci isolates, 16 (17.39%) were multidrug-resistant (MDR), primarily those from poultry (38.09%) and pork meat (21.05%). Resistance to fluoroquinolones was confirmed only in MDR enterococci isolates from poultry meat (28.57%). Resistance to vancomycin, ampicillin, linezolid, teicoplanin and tigecycline was not detected.